The Use of Renewable Energy Sources in Households in Poland—Current Status and Prospects for the Development of Energy Prosumption - Paulina Trębska; Marcin Wysokiński; Anna Trocewicz; Joanna Żurakowska-Sawa; Julia Tsybulska; Aleksandra Płonka; Piotr Bórawski; Aneta Bełdycka-Bórawska (Energies)
This article aimed to assess the use of renewable energy sources (RES) in households in Poland in the context of the Statistics Poland (GUS) research and our survey research. In addition, plans for using renewable energy sources and the willingness of respondents to spend money for this purpose were examined. At the beginning of this article, a theoretical approach to the household as an energy prosumer was presented, and the structure of obtaining energy from RES in Poland was shown. Then, the survey research methodology was presented, including the selection of the sample and the purpose of the survey. The next part of this article concerns the characteristics of the respondents and the buildings they inhabit, as well as statistics on RES used in the surveyed households. The research shows that 12% of the surveyed population was an energy prosumer, and 22% were interested in and planning to invest in RES. Only half of the respondents were ready to spend their money on micro-installations. The results were presented using the documentary and comparative methods. This article uses data from Statistics Poland (GUS) and our survey research conducted among 1112 representatives of households in Poland.